2022
DOI: 10.1097/md.0000000000031030
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant probiotic Bifidobacterium animalis subsp. lactis CP-9 improve phototherapeutic treatment outcomes in neonatal jaundice among full-term newborns: A randomized double-blind clinical study

Abstract: Background: Probiotics had been used to decreased bilirubin level in neonatal jaundice (NJ) without being further studied mechanism and stratification. The intestinal pathogen Escherichia coli produced β-glucuronidase would increase enterohepatic circulation and elevate serum bilirubin levels (SBLs) which might worsen the disease process of NJ. Study objective:We hypothesized that some probiotics could decrease bilirubin level through inhibiting the growth of E. coli. It's assumed that adjuvant probiotic inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…On the other hand, Nouri et al prescribed PediLact as a synbiotic in icteric term and preterm neonates > 35 weeks of GA and revealed significant differences in the rate of bilirubin reduction and duration of hospital stay in the intervention group (3). In numerous studies, the findings showed that the addition of oral probiotics/prebiotics/synbiotics to phototherapy is associated with a higher bilirubin reduction rate, reduced phototherapy duration, and shorter hospitalization (31)(32)(33)(34)(35). In addition, S. boulardii, in combination with phototherapy, was effective and safe in reducing bilirubin levels and duration of phototherapy in icteric premature infants in Hu et al's study (36).…”
Section: Probiotics Prebiotics and Synbioticsmentioning
confidence: 99%
“…On the other hand, Nouri et al prescribed PediLact as a synbiotic in icteric term and preterm neonates > 35 weeks of GA and revealed significant differences in the rate of bilirubin reduction and duration of hospital stay in the intervention group (3). In numerous studies, the findings showed that the addition of oral probiotics/prebiotics/synbiotics to phototherapy is associated with a higher bilirubin reduction rate, reduced phototherapy duration, and shorter hospitalization (31)(32)(33)(34)(35). In addition, S. boulardii, in combination with phototherapy, was effective and safe in reducing bilirubin levels and duration of phototherapy in icteric premature infants in Hu et al's study (36).…”
Section: Probiotics Prebiotics and Synbioticsmentioning
confidence: 99%